BELGOROD STATE TECHNOLOGICAL UNIVERSITY NAMED AFTER V.G. SHUKHOV: STRATEGIC OBJECTIVES, PRIORITIES, IMPLEMENTATION STAGES - Sergey N. Glagolev (Высшее образование в России)
In the interview, the University rector, Doctor of Economics, Professor Glagolev describes the place BSTU named after V.G Shukhov holds in Russian and world rankings. The strategic mission, goals and objectives of the University are designated. The paper describes the development and implementation of new education programs at theuniversity , the experience in training specialists by request of an employer. Draws attention to the international cooperation and the creation of venture educational centers. Examines the goals and objectives of the conception of cultural and educational work that is carried out at the university.